Implementation of The Kampus Mengajar Program in Strengthening Literacy and Numeracy: A Literature Review Study - Siti Aisyah; Eny Munisah (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Educational inequality in the 3T (United, Disadvantaged, and Transmigration) regions, particularly in literacy and numeracy, remains a serious challenge in Indonesian education. The government launched the Kampus Mengajar Program, which involves university students assisting needy schools. This study aims to analyze the implementation of the Kampus Mengajar Program in improving student literacy and numeracy and identify challenges encountered during its implementation. This study used a qualitative approach with a literature review method, analyzing 15 scientific articles from the Google Scholar database spanning 2020–2025. Data were collected through a systematic search using relevant keywords and then analyzed descriptively using a synthesis technique by comparing, grouping, and summarizing results from various sources. The results show that the Kampus Mengajar Program effectively improves students' literacy and numeracy skills through a technology-based learning approach, interactive methods, and strengthening a culture of literacy in schools. In addition, this program benefits students by developing teaching skills and adapting them to diverse educational environments. However, the implementation of this program faces obstacles such as limited infrastructure, access to technology, and suboptimal involvement of parents and teachers. The short duration of the program also limits its impact. Therefore, government, schools, and community support are needed to optimize its effectiveness. With proper evaluation and sustainable policies, the Kampus Mengajar Program has the potential to become an effective intervention model for improving the quality of education, particularly in strengthening literacy and numeracy as its primary foundation.